Epidemiology of Viral-associated Acute Lower Respiratory Tract Infection Among Children <5 Years of Age in a High HIV Prevalence Setting, South Africa, 2009–2012. Issue 1 (January 2015) - Cohen, Cheryl; Walaza, Sibongile; Moyes, Jocelyn; Groome, Michelle; Tempia, Stefano; Pretorius, Marthi; Hellferscee, Orienka; Dawood, Halima; Chhagan, Meera; Naby, Fathima; Haffejee, Summaya; Variava, Ebrahim; et al.
<x xml:space="preserve">Abstract</x> Background: Data on the epidemiology of viral-associated acute lower respiratory tract infection (LRTI) from high HIV prevalence settings are limited. We aimed to describe LRTI hospitalizations among South African children aged <5 years. Methods: We prospectively enrolled hospitalized children with physician-diagnosed LRTI from 5 sites in 4 provinces from 2009 to 2012. Using polymerase chain reaction (PCR), nasopharyngeal aspirates were tested for 10 viruses and blood for pneumococcal DNA. Incidence was estimated at 1 site with available population denominators. Results: We enrolled 8723 children aged <5 years with LRTI, including 64% <12 months. The case-fatality ratio was 2% (150/8512). HIV prevalence among tested children was 12% (705/5964). The overall prevalence of respiratory viruses identified was 78% (6517/8393), including 37% rhinovirus, 26% respiratory syncytial virus (RSV), 7% influenza and 5% human metapneumovirus. Four percent (253/6612) tested positive for pneumococcus. The annual incidence of LRTI hospitalization ranged from 2530 to 3173/100, 000 population and was highest in infants (8446–10532/100, 000). LRTI incidence was 1.1 to 3.0-fold greater in HIV-infected than HIV-uninfected children. In multivariable analysis, compared to HIV-uninfected children, HIV-infected children were more likely to require supplemental-oxygen [odds ratio (OR): 1.3, 95% confidence interval (CI): 1.1–1.7)], be hospitalized >7 days (OR: 3.8, 95% CI: 2.8–5.0) and had a higher case-fatality ratio (OR: 4.2, 95% CI: 2.6–6.8). In multivariable analysis, HIV-infection (OR: 3.7, 95% CI: 2.2–6.1), pneumococcal coinfection (OR: 2.4, 95% CI: 1.1–5.6), mechanical ventilation (OR: 6.9, 95% CI: 2.7–17.6) and receipt of supplemental-oxygen (OR: 27.3, 95% CI: 13.2–55.9) were associated with death. Conclusions: HIV-infection was associated with an increased risk of LRTI hospitalization and death. A viral pathogen, commonly RSV, was identified in a high proportion of LRTI cases.